Fruit Plants Species along Corridor in Kopendukuh Village as a Resource for Rural Tourism Development - Putri, Widya Kristiyanti; Naim, Abu; Setiawan, Hendra (Graduate School, Universitas Brawijaya, 2015)
This research aims to identify fruit plants species which is potential for tourism attraction, spatially describes fruit plants distribution and identify local people's response for fruit plants as tourims attraction in Kopendukuh village, Banyuwangi. Survey was done along the villages corridors. The fruit plant species along corridors was identified and mapped using GPS. Furthermore, semi-structural interview was used to gain informations of local people response about fruit plants as tourism attraction. There were about 18 species and 162 individuals were found along corridor of Kopendukuh village. Fruit plants always found in local home gardens along rural corridor. Local peoples argue that fruit planst s important for numerous purposes. Local people support tourism development in rural area which based on the fruit plants richness (i.e. agrotourism). Keywords: fruit plants, mapping, corridor, rural tourism.